2019
DOI: 10.2478/jomb-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glutamate dehydrogenase activity and efficacy of antipsychotic therapy in patients with schizophrenia

Abstract: Summary Background Evaluation of possible relationship between platelet glutamate dehydrogenase (GDH) activity and mental state of schizophrenia patients after antipsychotic pharmacotherapy. Methods Patients (n = 50) with chronic paranoid schizophrenia (F20.0) initially in acute psychotic state were examined before and after a treatment course with antipsychotics. When assessing the patients’ states using PANSS, the »responder« category was attributed to those patients who had not less than 30% reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…This further supports the importance of glutamate homeostasis, maintained by a multitude of metabolic and synaptic components, in cognitive function. This is the rst demonstration of a gene x environment interaction in mice with abnormal expression of Glud1, which is downregulated in schizophrenia 20 and predicts antipsychotic treatment e cacy 70 . Similarly to other psychiatric disorders, schizophrenia symptoms are believed to be "triggered" by an external event in individuals with underlying genetic susceptibility 71 .…”
Section: Discussionmentioning
confidence: 82%
“…This further supports the importance of glutamate homeostasis, maintained by a multitude of metabolic and synaptic components, in cognitive function. This is the rst demonstration of a gene x environment interaction in mice with abnormal expression of Glud1, which is downregulated in schizophrenia 20 and predicts antipsychotic treatment e cacy 70 . Similarly to other psychiatric disorders, schizophrenia symptoms are believed to be "triggered" by an external event in individuals with underlying genetic susceptibility 71 .…”
Section: Discussionmentioning
confidence: 82%
“…The largest number of studies on the importance of GDH in psychiatry relate to schizophrenia. Savushkina et al found that baseline GDH levels could serve as a predictor of the efficacy of antipsychotic therapy in patients with schizophrenia, as in that study, GDH activity significantly increased during post-antipsychotic treatment [201]. According to Burbaev et al, treatment with olanzapine affects the amounts of glutamate-metabolising enzymes in the platelets of patients with chronic schizophrenia.…”
Section: Gdh In Psychiatrymentioning
confidence: 76%
“…It was also found that the longer the disease lasted before starting the treatment cycle, the higher the GDH levels measured after treatment [202,203]. Baseline platelet GDH activity may serve as a predictor of the efficacy of antipsychotic therapy in patients with schizophrenia [201]. A review by Plaitakis on the topic of GDH deregulation in neurological diseases showed that GDH deregulation in schizophrenia remains an important issue to be addressed [204].…”
Section: Gdh In Psychiatrymentioning
confidence: 99%
“…Активность ГДГ определяли (только в тромбоцитах) по скорости снижения поглощения НАД•Н при 340 нм по методу Фишера [20] согласно ранее предложенным модификациям [21]. Активность ГР определяли по скорости окисления НАДФ•Н в реакции восстановления окисленного глутатиона [22].…”
Section: определение биохимических показателей кровиunclassified